ANALISIS PENGGUNAAN POLDER DAN KOLAM RETENSI PADA KAWASAN TANJUNG SENAI KABUPATEN OGAN ILIR - Rahmat Johar Syafei; Achmad Syarifudin; Ely Mulyati (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
This study aims to analyze flood discharge characteristics based on hydrological data and to assess the effectiveness of implementing a polder and retention pond system for flood control. The research methods include hydrological analysis using maximum annual rainfall data (2010–2023) from the Meteorology, Climatology, and Geophysics Agency (BMKG), frequency and distribution analysis (Normal, Log Normal, Gumbel, and Log Pearson Type III), distribution suitability testing, rainfall intensity calculations using the Mononobe formula, and determining the planned discharge using the rational method. The analysis results indicate that the rainfall data conforms to a normal distribution with a mean of 469.43 mm and a standard deviation of 93.44 mm. The planned discharge for a 50-year return period is 0.70 m³/s. The planned capacity of the polder and retention pond is sufficient to accommodate this discharge, thus this system is considered effective in reducing flood risk in the study areaKeywords: Polder, Retention Pond, Flood, Hydrology, Tanjung Senai